2021
DOI: 10.1063/5.0046205
|View full text |Cite
|
Sign up to set email alerts
|

Annealing effects on interdiffusion in layered FA-rich perovskite solar cells

Abstract: Annealing is one of the processing methods that are used for the fabrication of defect-free, photoactive perovskite films with compact grains in highly efficient and stable perovskite solar cells (PSCs). Thus, the annealing temperature is a key parameter for the control of the interdiffusion (of constituent elements) in photoactive films. In this paper, we present the results of a systematic study of the effects of annealing on the interdiffusion of constituent elements in efficient formamidinium-based PSCs. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Unless otherwise stated, most of the materials used in this work were purchased from Sigma Aldrich and used as received. Apart from Polyethylene Oxide (PEO) polymer, all the other materials have been listed in our previous work on FA-Rich PSC 13 , 55 57 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unless otherwise stated, most of the materials used in this work were purchased from Sigma Aldrich and used as received. Apart from Polyethylene Oxide (PEO) polymer, all the other materials have been listed in our previous work on FA-Rich PSC 13 , 55 57 .…”
Section: Methodsmentioning
confidence: 99%
“…After sequential cleaning of pre-patterned FTO-coated glass substrate in a detergent, acetone, and IPA, a compact electron transport layer (ETL) was formed from mixed titanium dioxide (TiO 2 ) and tin (iv) oxide (SnO 2 ) precursor solutions following the procedure described elsewhere 55 . The SnO 2 and TiO 2 in the ETL precursor solution was mixed in the volume proportion of 0.2 (optimized from previous work) before being spin coated onto the FTO coated glass substrate 57 .The perovskite active layer was formed on the ETL via a two-step spin-coating process where the lead (II) Iodide (0.5993 g in 1 ml of mixed DMF-DMSO solvent) was first spin-coated, followed by the organic components that were mixed with PEO in different weight proportions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To remove residuals, pre-etched FTO-coated (∼7 Ω/sq) glass slides (MSE Supplies, AZ) were cleaned successively in Decon-90, deionized water, acetone, and isopropyl alcohol for 15 min each and treated by UV–ozone exposure (Novascan, IA, USA). A compact TiO 2 (cTiO 2 ) electron transport layer (ETL, thickness of ∼100 nm) was formed using 0.15 and 0.3 M TiO 2 solutions as described elsewhere. , A mesoporous TiO 2 (mTiO 2 ) layer was subsequently spin-coated at 4000 rpm for 30 s with titania paste in ethanol (1:5, v/v) and calcined at 500 °C for 30 min …”
Section: Methodsmentioning
confidence: 99%
“…With the annealing of perovskite, the peak of mesophase gradually disappears, the diffraction peak of the perovskite α phase gradually increases, and the crystal orientation is obvious. Oyewole et al used scanning electron microscopy to test the surface morphologies annealed at different temperatures, as shown in Figure 14b [93], and the test results clearly showed that the annealing temperature would significantly affect the surface morphologies of perovskite films. The grain size of the perovskite film annealed at 100 • C is small, and the grain size increases with the gradual increase in temperature.…”
Section: Effect Of Annealing Temperature On Perovskite Materialsmentioning
confidence: 99%